AB0601 UTILIZATION OF A MULTISPECIALTY TEAM FOR THE DIAGNOSIS OF GIANT CELL ARTERITIS REDUCES PATIENT MORBIDITY. (June 2019) - Hassantoufighi, Arash; Lu-Do, Rachel; Dhillon, Joshpaul; Collins, Christopher; Constantinescu, Florina
Abstract : Background: Giant Cell arteritis (GCA) is an autoimmune vasculitis, most commonly seen in older adults with a peak incidence in the seventh decade of life. A diagnosis of GCA is often considered in any patient over the age of 50 years who complains of or is found to have new onset headache, acute visual disturbances, jaw claudication, unexplained fever, or elevated inflammatory markers. Because the manifestations of GCA can vary considerably from patient to patient, often with transient and fluctuating symptoms, an accurate diagnosis can be challenging. Even in the setting of a negative temporal artery biopsy, many patients are treated empirically based on the perceived probability of disease. This approach can lead to significant morbidity from prolonged medication exposure and unnecessary procedures. Objectives: The aim for this project was to look at the impact of a collaborative effort amongst three specialties, rheumatology neurology and ophthalmology, which composed a consultation based "GCA team", the goal of which was to improve how GCA is diagnosed and subsequently managed. Methods: We conducted a retrospective study of all patients suspected to have GCA at our institution over the last 2.5 years that had either been seen by the GCA team or not. The GCA team met either in person or had a conference call to discuss each case and make a joint decision regarding the diagnosis and treatment. Data extracted included patient demographics, symptoms on presentation, labs, biopsy results and accumulative prednisone dose. Results: A total of 30 patients (19 female, 11 male) were evaluated; 19 were seen by the GCA team and 11 were not. The mean ages of the patients in each group were the similar (GCA Team 70.6 (SD 12.5) vs no GCA Team 70.3 (SD 12.3)). The mean ESR between the two groups was also similar (GCA Team 53.3 (SD 30.2) vs no GCA Team 53.8 (SD 27.2)). The presenting clinical symptoms between the two groups were also comparable: visual complaints (63% vs 73%), headache/jaw claudication/temporal artery tenderness (42% vs 45%), and cranial neuropathy (11% vs 9%). All of the patients not seen by the GCA team underwent bilateral temporal artery biopsy; however none were positive on histology. Regardless, all were continued on high dose prednisone with a 6 month cumulative mean dose of 5, 350mg. Of the 19 patients seen by the GCA team, 8 were determined to be low probability for GCA and thus were spared temporal artery biopsy. Furthermore, all of the patients were recommended a rapid steroid taper and the cumulative mean dose of prednisone was only 490mg. Over 6 months of follow-up, none of the 8 patients deemed low probability had a subsequent diagnosis of GCA given. Compared to patients deemed high probability by the GCA team, low probability patients were younger (68.6 vs 71.2), more often female (75% vs 45%), had lower ESR (40.5 mm/hr vs 66.1 mm/hr), and presented with more visual complaints (86% vs 46%). In the 11 high probability GCA patients, 10 underwent temporal artery biopsy (one refused) with 4 biopsies read as positive for GCA. Over 6 months of follow up, none of these patients had flares after they were started on treatment. Conclusion: While the accuracy of a GCA diagnosis cannot be determined in our cohort of patients not seen by the GCA team, it is likely that evaluation by a multispecialty team would have found several to be low probability for GCA, especially as none of the patients had a positive temporal artery biopsy. We have demonstrated that by adopting a collaborative approach to diagnosing GCA, unnecessary biopsies can be avoided as well as limiting unnecessary prednisone exposure. More prospective data is needed to provide an accurate assessment of this team approach for GCA which can serve as a model for other healthcare facilities. Disclosure of Interests: Arash Hassantoufighi: None declared, Rachel Lu-Do: None declared, Joshpaul Dhillon: None declared, Christopher Collins Grant/research support from: Exagen, Consultant for: Exagen, abbVie, Speakers bureau: Exagen, abbVie, Novartis, Florina Constantinescu: None declared